Determine the Factors Affecting the Quality of Internal Shariah Audits: A Review Paper on Islamic Banking in Libya - Adel K. Alghamati; S. M. Ferdous Azam; Ali Khatibi (Journal of Business and Social Review in Emerging Economies)
Purpose: The present research will offer a theoretical framework discussing the concept of internal Shariah audit quality and identifying the factors that affect it. The study aims to examine these elements and their relationship with the internal Shariah audit quality in Islamic banking in Libya.